Wood and bark of Prosopis alba Griseb., algarrobo blanco, Mimosaceae, in relation to some dendrometric magnitudes - Gimenez, Ana María; Rios, Norfol; Moglia, Graciela; López, Carlos (Bosque (Valdivia), 1998)
Prosopis alba Griseb., is one of the most important Argentinean Mimosaceae. With a great distribution area, it is a common component in the Chaco Forest. Prosopis alba, "Algarrobo blanco", is one of the Argentina's legumes of more economic importance. The aims of this study are: to describe the wood and bark anatomy and tree ring pattern of Prosopis alba, to analyse tree ring evolution in relation to age and orientation, to characterise sapwood, heartwood and bark width, in relation to age, DBH (diameter at breast height) orientation, and height and to determine the main defects of the wood. The study was carried out in ten individuals from the following sites of Santiago del Estero, Argentina: Brea Pozo, San Martín Department; Las Delicias, Pellegrini Department and Sachayoj, Alberdi Department. Healthy, well formed trees, with more than 30 cm DBH were selected from the dominant-canopy. Wood samples were taken following the methodology of Helinska et al. The terminology by IAWA was used for wood descriptions, and the terminology by Roth in bark. Results obtained show that Prosopis alba has tree ring demarcated by terminal parenchyma (type 2 of Coster). Tree rings have a medium width of 4.05 mm (2.11-5.18), with a maxim between 29 and 32 years. Orientation had no influence on width. Sapwood in the trunk has a tree ring width (2-6), diminishing with age and height. The principal defect of the wood are the scars produced by fire which alter the pattern of growth. The deciduous bark is of the fibrous type, with longitudinal fissures. The thickness of total bark is 1.16 cm, the living bark 0.39 cm and rhytidome 0.74 cm. The bark increases with age and diminishes with DBH. The duraminization process begins between the years 3 to 6.